2018
DOI: 10.1002/hep.29920
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma cell‐secreted exosomal microRNA‐103 increases vascular permeability and promotes metastasis by targeting junction proteins

Abstract: Hepatoma cell-secreted exosomal miR-103 increases vascular permeability and promotes tumor metastasis by targeting multiple endothelial junction proteins, which highlights secreted miR-103 as a potential therapeutic target and a predictive marker for HCC metastasis. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(204 citation statements)
references
References 37 publications
2
196
0
Order By: Relevance
“…In this scenario, exosomal miRNAs seem to play relevant roles as metastasis-promoting factors. In HCC, the high levels of serum miR-103a-3p are associated with patients with metastasic episodes [102]. This exosomal miRNA, released by liver cancer cells, is able to attenuate the junction integrity of recipient endothelial cells (HUVEC) by targeting adhesion molecules such as VE-cad, p120, and zonula occludens 1 (ZO-1), thus increasing the vascular permeability both in vivo and in vitro [102].…”
Section: The Cellular Crosstalk In the Tumor Microenvironment Promotementioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, exosomal miRNAs seem to play relevant roles as metastasis-promoting factors. In HCC, the high levels of serum miR-103a-3p are associated with patients with metastasic episodes [102]. This exosomal miRNA, released by liver cancer cells, is able to attenuate the junction integrity of recipient endothelial cells (HUVEC) by targeting adhesion molecules such as VE-cad, p120, and zonula occludens 1 (ZO-1), thus increasing the vascular permeability both in vivo and in vitro [102].…”
Section: The Cellular Crosstalk In the Tumor Microenvironment Promotementioning
confidence: 99%
“…In HCC, the high levels of serum miR-103a-3p are associated with patients with metastasic episodes [102]. This exosomal miRNA, released by liver cancer cells, is able to attenuate the junction integrity of recipient endothelial cells (HUVEC) by targeting adhesion molecules such as VE-cad, p120, and zonula occludens 1 (ZO-1), thus increasing the vascular permeability both in vivo and in vitro [102]. The subsequent tumor cell transendothelial motility process is promoted by exosomal miR-25-5p [103].…”
Section: The Cellular Crosstalk In the Tumor Microenvironment Promotementioning
confidence: 99%
“…Angiogenesis is also valuable in accelerating HCC proliferation. Fang et al . sequenced and quantitated PCR and found that HCC cell‐derived exosomes transmitted miR‐103 into endothelial cells attenuated the endothelial junction integrity by downregulating VE‐Cadherin (VE‐Cad), p120‐catenin (p120) and zonula occludens 1 (Table ).…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…Angiogenesis is also valuable in accelerating HCC proliferation. Fang et al 53 sequenced and quantitated PCR and found that HCC cell-derived exosomes transmitted miR-103 into endothelial cells attenuated the endothelial junction integrity by downregulating VE-Cadherin (VE-Cad), p120-catenin (p120) and zonula occludens 1 (Table 1). Also, there is emerging evidence indicating that HCC-derived exosomal miR-21 targeting PTEN led to the activation of PDK1/AKT signaling in HSCs, which educated CAFs released angiogenic cytokines, including VEGF, MMP2, MMP9, bFGF and TGF-beta (Table 1).…”
Section: Cancer Metastasismentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) cells use EV for the transfer of miRNA, long non‐coding RNA (lncRNA) and protein factors implicated in cancer development, migration and chemotherapy resistance to other HCC cells, to hepatocytes but also to endothelial cells and to fibroblasts . Fang et al reported that metastatic HCC cell lines (MHCC97H and QGY‐7703) exhibited increased production of EV containing miRNA‐103, identified as exosomes; when transferred to endothelial cells (LSEC, SK‐Hep‐1 and HUVEC), these EV increased in vitro the permeability of endothelial cell monolayers and reduced cell junctions integrity by a an interference with VE‐cadherin, p120 and ZO‐1 proteins . Interfering with exosome trafficking or using miRNA‐103 inhibitor RNA alleviated the effect of these EV on endothelial cells.…”
Section: Extracellular Vesicles In Chronic Liver Diseasesmentioning
confidence: 99%